(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of hypothermia and associated factors among newborns weighing ≤1500 grams admitted to the Neonatal Intensive Care Unit (NICU) of Children’s Hospital 2 during a six-month period (March 1, 2024 – September 30, 2024). Subjects and Methods: This was a prospective descriptive study involving neonates weighing ≤1500 grams at the time of admission to the NICU of Children’s Hospital 2 during the study period. Results: The study found that 51.3% of the infants were male and 48.7% female. The majority (76.9%) were from provinces outside Ho Chi Minh City. Of all neonates, 62.9% were transferred from lower-level facilities and directly admitted to the NICU. Regarding body temperature at admission, 20.5% had normal body temperature, while 79.5% presented with hypothermia. Of these, 53.8% had mild hypothermia, 23.1% moderate hypothermia, and 2.6% severe hypothermia. The average time for body temperature to return to normal was 1.79 hours. Conclusion: A significant number of preterm, low birth weight newborns continue to be transferred between facilities after birth. Most of these infants are referred from other provinces and directly admitted from other hospitals to the NICU. Maintaining thermal stability during transport remains a major challenge, with a high proportion of neonates presenting with hypothermia upon admission.